Computed tomographic arthrography, gross anatomy and histology demonstrate a communication between synovial invaginations in the proximal aspect of the third interosseous muscle and the carpometacarpal joint in horses - Gerdes, Carolin; Morgan, Rhiannon; Terry, Rebecca; Foote, Alastair; Smith, Roger (Frontiers in Veterinary Science, 2022)
This descriptive anatomical study investigates the relationship between the proximal suspensory ligament and the carpometacarpal joint in forelimbs of horses with the hypothesis that there was a direct synovial communication between these structures as shown by computed tomographic arthrography, histology and gross anatomy sections. Computed tomography of the carpus and metacarpal region was performed on sixteen forelimbs divided into two groups. Group 1 consisted of 8 cadaver limbs undergoing computed tomographic arthrography following injection of a mixture of positive contrast media, saline and color-pigmented fluid solution into the middle carpal joint. Group 2 were 8 forelimbs assessed with plain computed tomography. Images were interpreted subjectively for contrast distribution and objectively by comparing Hounsfield values of the proximal suspensory ligament at 0.5cm intervals starting at the origin and extending 3cm distal to the proximal subchondral bone plate of the third metacarpal bone. Of the 16 limbs, 2 were sectioned for gross anatomy and 1 was evaluated histologically. The proximal suspensory ligament was visualized with clear margins on computed tomography images. Positive contrast medium was found within the lateral and medial lobes of the suspensory ligament in 8/8 (100%) of the limbs. Hounsfield units within the suspensory ligament following contrast injection were significantly higher than in the control group between 0.5cm and 2.5cm distal to the proximal subchondral bone plate of the third metacarpal bone (p<0.05). Gross anatomy sections showed color pigmentation within the suspensory ligament correlating to the contrast distribution evident on computed tomography images. Histology confirmed a synovial lined cavity within the suspensory ligament. The demonstration of a direct synovial communication between the internal structure of the proximal suspensory ligament and the carpometacarpal joint in horses offers further explanation for commonly encountered interactions of diagnostic local anesthesia of the carpal and subcarpal regions. When performing diagnostic or therapeutic injections into the middle carpal joint, the likely effect on the proximal suspensory ligament should be considered. Furthermore, as the proximal suspensory ligament was identified clearly on CT images, further studies are needed to elucidate the utility of CT in clinical cases with suspected soft tissue pathology in the subcarpal region.